2009
DOI: 10.1002/mrc.2393
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR assignments of eight nitrogen containing compounds from Nocardia alba sp.nov (YIM 30243T)

Abstract: An unprecedented new natural product named nocarsin A (1), 5H-4a,6,7a-triazacyclopenta[cd]indene-5,7(6H)-dione (1), together with seven known compounds lumichrome (2), cyclo (L-Leu-L-Tyr) (3), cyclo (L-Ala-L-Ile) (4), cyclo (L-Ala-L-Leu) (5), cyclo (L-Val-L-Ala) (6), 5-methyluracil (7) and uracil (8), was isolated from Nocardia alba sp.nov (YIM 30243(T)), which was isolated from a soil sample collected from Yunnan Province, P. R. China. NMR techniques including COSY, HSQC, ROESY, and HMBC were used to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 6 publications
4
26
0
Order By: Relevance
“…J. endophytica 161111 was found to produce alkaloids in a saline culture medium by thin layer chromatography (TLC) visualizing with Dragendorff’s reagent. Chemical investigations on the ethyl acetate (EtOAc) extract of fermentation broth of strain 161111 resulted in the isolation and identification of three pyrazine derivatives, 2-(furan-2-yl)-6-(2 S ,3 S ,4-trihydroxybutyl)pyrazine ( 1 ) and 2-(furan-2-yl)-5-(2 S ,3 S ,4-trihydroxybutyl) pyrazine ( 2 ) [6] and lumichrome ( 10 ) [7]; four pyrrololactones, ( S )-4-isobutyl-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 3 ) [8], ( S )-4-isopropyl-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 4 ) [8], (4 S )-4-(2-methylbutyl)-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 5 ) [8,9] and ( S )-4-benzyl-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 6 ) [10]; three β-carbolines, flazin ( 7 ) [11], perlolyrine ( 8 ) [12] and 1-hydroxy-β-carboline ( 9 ) [13]; along with 1 H -indole-3-carboxaldehyde ( 11 ) [14,15], 2-hydroxy-1-(1 H -indol-3-yl) ethanone ( 12 ) [14,15], and 5-(methoxymethyl)-1 H -pyrrole-2-carbaldehyde ( 13 ) [16] (Figure 1). Compounds 8 – 11 showed anti-influenza A (H1N1) virus activity with the half maximal inhibitory concentration ( IC 50 ) and selectivity index ( SI ) values of 38.3(±1.2)/25.0(±3.6)/39.7(±5.6)/45.9(±2.1) μg/mL and 3.0/16.1/3.1/11.4, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…J. endophytica 161111 was found to produce alkaloids in a saline culture medium by thin layer chromatography (TLC) visualizing with Dragendorff’s reagent. Chemical investigations on the ethyl acetate (EtOAc) extract of fermentation broth of strain 161111 resulted in the isolation and identification of three pyrazine derivatives, 2-(furan-2-yl)-6-(2 S ,3 S ,4-trihydroxybutyl)pyrazine ( 1 ) and 2-(furan-2-yl)-5-(2 S ,3 S ,4-trihydroxybutyl) pyrazine ( 2 ) [6] and lumichrome ( 10 ) [7]; four pyrrololactones, ( S )-4-isobutyl-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 3 ) [8], ( S )-4-isopropyl-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 4 ) [8], (4 S )-4-(2-methylbutyl)-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 5 ) [8,9] and ( S )-4-benzyl-3-oxo-3,4-dihydro-1 H -pyrrolo[2,1- c ][1,4]oxazine-6-carbaldehyde ( 6 ) [10]; three β-carbolines, flazin ( 7 ) [11], perlolyrine ( 8 ) [12] and 1-hydroxy-β-carboline ( 9 ) [13]; along with 1 H -indole-3-carboxaldehyde ( 11 ) [14,15], 2-hydroxy-1-(1 H -indol-3-yl) ethanone ( 12 ) [14,15], and 5-(methoxymethyl)-1 H -pyrrole-2-carbaldehyde ( 13 ) [16] (Figure 1). Compounds 8 – 11 showed anti-influenza A (H1N1) virus activity with the half maximal inhibitory concentration ( IC 50 ) and selectivity index ( SI ) values of 38.3(±1.2)/25.0(±3.6)/39.7(±5.6)/45.9(±2.1) μg/mL and 3.0/16.1/3.1/11.4, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…8 In this study, the perylenequinones showed antileishmanial, antiplasmodial, and cytotoxic activities in addition to antibacterial and antifungal activities. Two more known compounds, lumichrome, 9 and brassicasterol 10 were also isolated and identified.…”
mentioning
confidence: 99%
“…Finally, a new compound, arecine (1), together with twenty known diketopiperazines, cordysinin A (2), [17] cyclo(l-Thr-l-Pro) (3), [18] cyclo(6-hydroxy-Pro-l-Leu) (4), [19] cyclo(l-Val-l-Pro) (5), [20] bacillusamide B (6), [21] cyclo(l-Leu-l-Pro) (7), [20] cyclo(l-Val-l-Ala) (8), [22] cyclo(l-Leu-l-Ala) (9), [23] cyclo(l-Ile-l-Ala) (10), [22] cyclo(Gly-l-Val) (11), [24] cyclo(Gly-l-Leu) (12), [25] cyclo(Gly-l-Ile) (13), [26] cyclo(l-Ile-d-Pro) (14), [27] staphyloamide A (15), [19] cyclo(l-Ala-l-Pro) (16), [20] cyclo(l-Ser-l-Pro) (17), [28] cyclo(l-Trp-l-Pro) (18), [29] cyclo(l-Tyr-l-Pro) (19), [30] cyclo(l-Phe-l-Ala) (20), [31] and cyclo(l-Ser-l-Phe) (21) [32] were identified. On the other hand, the fungus D. arecae was also cultured by the PDB condition with 10 % NaCl in room temperature for two weeks.…”
Section: Resultsmentioning
confidence: 99%